Original article Combined therapy: surgery and intraoperative HDR brachytherapy for locally advanced and recurrent rectal cancer. Practical experience of Brachytherapy Department in Warsaw - Gierej, Piotr; Radziszewski, Jakub; Łyczek, Jarosław; Kawczyńska, Maria; Kulik, Anna (Journal of Contemporary Brachytherapy, 2009)
Purpose: Patients with locally advanced and recurrent rectal cancer have a dismal prognosis. The aim of proposed combined therapy – surgery and intraoperative brachytherapy, is to improve results of already applied methods and to define optimal group of patients for this treatment. We introduce practical experience of Brachytherapy Department in Cancer Centre – Institute in Warsaw. Material and methods: Patients with primary T4NxM0 rectal cancer and isolated local pelvic recurrence were qualified for therapy. Between January 2005 and September 2008, 13 patients were included: 4 with primary cancer and 9 with recurrence, median age of 56. After surgical resection intraoperative radiotherapy was delivered with boost of high dose rate brachytherapy of 20Gy dose to the tumor bed. Results: Primary point of the study is to evaluate impact of applied therapy on local control (LC), overall survival (OS) and disease free survival (DFS). Median follow-up is 16 months. Four of the patients died and 3 survivors are disease-free. There was no case of perioperative mortality. Conclusions: A multimodality approach, using surgical resection with intra operative brachytherapy improves local control as well as patients survival in comparison with historical treatment group. Combined therapy is related to high morbidity, but low mortality. The preliminary observations seem to correspond with other authors data.